Code Mixing Used by Characters in Grand Theft Auto V (GTA V) (e-Journal of Linguistics, 2026)
Code mixing has become an important topic in sociolinguistics because it reflects how multilingual speakers construct identities and negotiate social relationships. However, its representation in commercial video games remains underexplored. This study investigates the types of English–Spanish code mixing in the dialogues of Grand Theft Auto V (GTA V) and the social factors influencing its variation. Using a qualitative descriptive approach, the study analyzed 14 dialogue excerpts collected from gameplay recordings, selected missions, and cinematic cutscenes. Data were gathered through documentation and systematic note-taking and analyzed using Poplack’s code-mixing classification and the Identity and Interactional Sociolinguistics framework. The findings identify three types of code mixing: intra-sentential, inter-sentential, and tag code mixing. Their occurrence is shaped by ethnicity, regional background, situational context, and social networks, demonstrating that language choice functions as a strategic resource for constructing identities and social relationships rather than as random language alternation. This study extends sociolinguistic research into digital narrative discourse by highlighting video game dialogue as a valuable source for examining multilingual practices and identity construction.